Cholesterol and Triglycerides in Antipsychotic-Naive Patients with Nonaffective Psychosis - Kirkpatrick, Brian (2010)
Patients with psychosis have an increased prevalence of hyperlipidemia. We compared fasting concentrations of lipids in newly diagnosed, antipsychotic-naïve patients with nonaffective psychosis (N-87) and control subjects (N=92). After accounting for gender, age, smoking, socioeconomic status, and body mass index, there was no significant difference between the two groups in total cholesterol, high-density lipoproteins, low-density lipoproteins, or triglycerides.